Sexual dimorphism in synaptic inputs to the mouse amygdala and orbital cortex - Aloni, Etay; Tibi, Muhammad; Hochgerner, Hannah; Zeisel, Amit (Frontiers in Neuroscience, 2023)
The medial amygdala (MeA) is a sexually dimorphic brain region that regulates fear responses, emotional memories, and social behaviors. It is known to be larger and contains more cells in males. The MeA integrates information through input connections from olfactory regions, bed nucleus of the stria terminalis, ventral hippocampus, and thalamic and hypothalamic structures. We hypothesize that in addition to the size differences, there are differences in regional connectivity between the sexes. In this study, we utilized G-deleted rabies monosynaptic retrograde tracing to compare amygdala presynaptic cells in male and female whole mouse brains. We report differences in connection patterns to the amygdala, with higher overall connectivity (presynaptic per starter) in males and a larger fraction of inputs originating from the bed nucleus of the stria terminalis, lateral septum, and medial preoptic area. Furthermore, we examined input connections to the orbital cortex (ORB), a brain region shown to be larger in volume in females, and found the opposite trend, where females had more total inputs. Together, our findings extend the evidence for sexual dimorphism in the brain to the neuronal wiring pattern, with likely impacts on behavior and disease susceptibility.